CRISPR-Cas-Based Diagnostic Tools for Companion Birds: An Overview - J, Juana Darlene Virgit; Anitha, Deepika; Angamuthu, Raja (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Though pet bird ownership is increasing substantially, avian medicine faces a unique diagnostic challenge as birds often conceal signs of illness until the disease has progressed beyond treatment possibilities. Current diagnostic tools, such as qPCR and ELISA, are promising but rely heavily on expensive equipment and trained personnel. This results in long turn-around times, which makes them unsuitable for rapidly progressing avian diseases. This review evaluates the potential of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) and CRISPR-associated (Cas) systems to overcome these limitations. By utilizing the "collateral cleavage" activity of Cas12 and Cas13 nucleases, these platforms offer the sensitivity of qPCR with the speed and portability of point-of-care tools. The review also describes recently validated CRISPR-Cas-based models for poultry diseases such as Avian Leukosis Virus, Infectious Bronchitis Virus, and Duck Hepatitis A Virus and analyses their potential for translation into companion bird diseases. Further, the possibility of CRISPR-Cas to aid in detection of zoonotic threats like Psittacosis and Avian Influenza, alongside a few other critical avian pathogens is described. Despite challenges such as aerosol contamination and sample preparation, CRISPR-Cas systems combined with isothermal amplification represent a significant step toward accessible, lab-quality diagnostics for veterinarians, pet owners, and breeders.
Keywords: Avian medicine; Companion birds; CRISPR-Cas; Point-of-care diagnostics; Zoonotic diseases